Design, fabrication and characterization of SiO2/TiO2 and MgO/TiO2 based high selective optical filters for spectroscopic signals extraction - Pimenta, Sara (2015)
Spectroscopic techniques, specifically diffuse reflectance and fluorescence, can considerably improve the ability to detect Gastrointestinal (GI) dysplasia, since they have exquisite sensitivity to the cancer biomarkers present on the tissues. Therefore, the development of a spectroscopic microsystem on a chip will have a high clinical value, since it could be integrated with the conventional endoscopes and colonoscopes, helping in the detection of GI dysplasia.